2011
DOI: 10.1093/annonc/mdr004
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of carboplatin and etoposide in patients with anaplastic progressive metastatic castration-resistant prostate cancer (mCRPC) with or without neuroendocrine differentiation: results of the French Genito-Urinary Tumor Group (GETUG) P01 trial

Abstract: The benefit-risk ratio of this regimen seems unfavorable due to poor response and high toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 22 publications
3
100
0
6
Order By: Relevance
“…NE variation was different according to the markers, with a higher decrease rate for NSE than CgA. This treatment seemed to be more active on NSE than CgA; this was in accordance with the results reported by Fléchon et al [31 ]that showed an NSE decrease for 31% of cases and a CgA decrease for 7%. Moreover, docetaxel/prednisone and curcumin acted similarly on PSA and tumor response regardless of the NE features (elevated or not).…”
Section: Discussionsupporting
confidence: 90%
“…NE variation was different according to the markers, with a higher decrease rate for NSE than CgA. This treatment seemed to be more active on NSE than CgA; this was in accordance with the results reported by Fléchon et al [31 ]that showed an NSE decrease for 31% of cases and a CgA decrease for 7%. Moreover, docetaxel/prednisone and curcumin acted similarly on PSA and tumor response regardless of the NE features (elevated or not).…”
Section: Discussionsupporting
confidence: 90%
“…Of 41 patients treated, 13 (33%) obtained a serum NE marker response (>50% decrease of neuron specific enolase or chromogranin A). This study demonstrates that the association of etoposide and either cisplatin or carboplatin is active in poorly differentiated NE cancers (4). Another study performed by Fjällskog et al (5) also demonstrates that the combination of cisplatin and etoposide can produce significant responses in patients with heavily pretreated and poorly differentiated/rapidly progressing NE tumors.…”
Section: Introductionsupporting
confidence: 59%
“…In a subsequent report studying docetaxel plus carboplatin, the objective response rate was 25% in chemonaive patients who also received with estramustine, and 8% in patients progressing despite docetaxel. 17 Fléchon and colleagues 18 studied etoposide and carboplatin in a phase II trial enrolling men with visceral metastase and/or elevated neuroendocrine markers. Of the 56 patients, 37% had liver metastases and the objective response rate in patients with visceral metastases was 8.9%.…”
Section: Discussionmentioning
confidence: 99%